Does endurance training improve red blood cell aging and hemorheology in moderate-trained healthy individuals? - Bizjak, Daniel A. (J Sport Health Sci, 2020)
OBJECTIVE: To examine the impact of a 6-week endurance training on red blood cell (RBC) aging and deformability of healthy participants to detect possible improved hemorheological and performance-related adaptations. METHODS: A total of 31 participants (17 females and 14 males) performed a 6-week moderate training protocol (three 1-h running sessions per week at 70% of maximal heart rate). Blood was sampled before and after the training. RBCs from each participant were fractioned according to density and age into 4 RBC subfractions. Subfractions were examined for changes of RBC properties, including aging distribution, RBC deformability, RBC microparticles, and phosphatidylserine concentrations. RBC and plasma nitrite levels were measured as indicators of nitric oxide metabolism. RESULTS: Aerobic performance, peak oxygen consumption, ventilatory thresholds, velocity at the aerobic–anaerobic threshold, and lactate at exhaustion improved after training. The relative amount of both young RBCs and old RBCs increased, and the amount of the main RBC fraction decreased. Phosphatidylserine externalization and RBC-derived microparticles decreased. Overall deformability expressed as shear stress required to achieve half-maximum deformation to theoretical maximal elongation index at infinite shear stress improved in unfractioned RBCs (p < 0.001). Nitrite decreased in total (p = 0.001), young (p < 0.001), main (p < 0.001), and old (p = 0.020) aged RBCs and in plasma (p = 0.002), but not in very old RBCs. CONCLUSION: These results indicate that non-endurance-trained healthy participants benefit from a regular moderate running training program because performance-related parameters improve and a younger RBC population with improved RBC properties is induced, which might support oxygen supply in the microcirculation.